WOMEN WRITERS IN ENGLISH LITERATURE (Journal of Universal Science Research, 2024)
This paper focuses on the woman writers in the English literature and their strong writing as well. The most important women authors will be portrayed. The paper will also explore the economic, social, political and other circumstances that determined their writing and try to represent their lives, their agony, their struggles, their writing and the styles they used especially in essays that reach beyond a reading of a single text in order to challenge existing thinking or extend debates about an author, genre, topic, or theoretical viewpoint and relate literary analysis to wider cultural and intellectual contexts. Gender plays an important role in the lives of human beings. From the very first breath of their life, humans were taught to follow a strict code of behavior that differs depending on their sex. In a patriarchal society, this often means that a male will lead a dominated privileged life in which he has thought to be the standard for human experience and the female will lead a subordinate, submissive life in which she is defined only in relation to males. Both patriarchy and imperialism could be seen to exert different forms of domination over those subordinate to them. Because of this, it was important for the experiences of women under the patriarchal influence to come out to the forefront and reveal the undue cruelty be held on them by men. It was necessary for the women to protest against this male dominance over them. We observe that women continue to define the borders of the community, class and race. They tried to express their agony and dissatisfaction of male dominated attitudes through their works. Moreover , The view on the feminine issues depended on the economical and living conditions that women writers went through, their education, social environment, the attitude toward tradition and the issue of women's independence. Whether the starting point for readers is literary and cultural studies, critical theory, or the canon of literary writings and its traditions, the agendas that have now been argued by feminist theories and explored in women's writings, cannot now be silenced or suppressed. Yet we still inhabit a world in which the reality for many women is that they remain second-class citizens and many women suffer horrific violence and injustice. Therefore, there is still a crucial and immediate need to publish new scholarly critical work, which will help men and women to reconsider their past gender identities, and equally significant, to review their futures.